EVALUASI KINERJA INSTALASI PENGOLAHAN AIR LIMBAH (IPAL) DI RUMAH SAKIT X BERDASARKAN PERBANDINGAN KUALITAS AIR INLET DAN OUTLET DENGAN PENDEKATAN DATA TEMPORAL BERBEDA - Nabila Nalalizza Mahmud; Nindy Callista Elvania (Fruitset Sains : Jurnal Pertanian Agroteknologi, 2026)
Hospital wastewater treatment plays a crucial role because it directly impacts environmental quality and public health, particularly due to its potentially hazardous pollutant content. This study aimed to assess the effectiveness of the Wastewater Treatment Plant (WWTP) at Hospital X by comparing the quality of wastewater at the inlet and outlet. The method used was a quantitative descriptive approach with data collection techniques in the form of field observations, sampling, and laboratory tests. Air samples were analyzed based on physical, chemical, and microbiological parameters, namely Total Suspended Solids, pH, Biological Oxygen Demand, Chemical Oxygen Demand, ammonia, and total coliform. The analysis results showed a decrease in concentrations of most parameters after the treatment process, with efficiencies of 66.59% for Total Suspended Solids, 88.89% for Biological Oxygen Demand, and 91.27% for Chemical Oxygen Demand. The pH value was still within the quality standards. However, the ammonia concentration increased, although still below the permissible limit. Overall, the WWTP performance was considered effective in reducing the pollutant load, and the treated wastewater met applicable standards, although optimization of the nitrification process was required.